2020
DOI: 10.3390/ijms21134729
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots in Plasmodium and RBC Receptor-Ligand Interactions: Key Pieces for Inhibiting Malarial Parasite Invasion

Abstract: Protein-protein interactions (IPP) play an essential role in practically all biological processes, including those related to microorganism invasion of their host cells. It has been found that a broad repertoire of receptor-ligand interactions takes place in the binding interphase with host cells in malaria, these being vital interactions for successful parasite invasion. Several trials have been conducted for elucidating the molecular interface of interactions between some Plasmodium falciparum and Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 119 publications
(261 reference statements)
1
18
0
Order By: Relevance
“…The list of essential merozoite proteins for the invasion process is extensive, including merozoite surface proteins (MSPs), erythrocyte-binding-like (EBL) and reticulocyte-binding-like (RBL) families, erythrocyte-binding antigen (EBA) and Rh protein family, P . falciparum reticulocyte-binding homolog 5 ( Pf Rh5)/PfRh5-interacting protein ( Pf Ripr)/cysteine-rich protective antigen (CyRPA) complex, rhoptry neck (RON) proteins, apical membrane antigen-1 (AMA-1), glycosylphosphatidylinositol-anchored micronemal antigen (GAMA), S-antigen, glutamate-rich protein (GLURP), serine-repeat antigen protein (SERA), claudin-like apicomplexan microneme protein (CLAMP), subtilisin-like serine protease (SUB), calcium-dependent protein kinases (CDPKs), glideosome-associated proteins (GAPs), myosin A, profilin, and cofilin [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Alterations in the function of these proteins by knockout gene expression or blocking (with inhibitors or antibodies) affect merozoite invasion efficiency and may inhibit parasite invasion [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The list of essential merozoite proteins for the invasion process is extensive, including merozoite surface proteins (MSPs), erythrocyte-binding-like (EBL) and reticulocyte-binding-like (RBL) families, erythrocyte-binding antigen (EBA) and Rh protein family, P . falciparum reticulocyte-binding homolog 5 ( Pf Rh5)/PfRh5-interacting protein ( Pf Ripr)/cysteine-rich protective antigen (CyRPA) complex, rhoptry neck (RON) proteins, apical membrane antigen-1 (AMA-1), glycosylphosphatidylinositol-anchored micronemal antigen (GAMA), S-antigen, glutamate-rich protein (GLURP), serine-repeat antigen protein (SERA), claudin-like apicomplexan microneme protein (CLAMP), subtilisin-like serine protease (SUB), calcium-dependent protein kinases (CDPKs), glideosome-associated proteins (GAPs), myosin A, profilin, and cofilin [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Alterations in the function of these proteins by knockout gene expression or blocking (with inhibitors or antibodies) affect merozoite invasion efficiency and may inhibit parasite invasion [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contributing to the formulation of preventative and/or therapeutic approaches which will assist in minimising the effects of malaria, there is a requirement of deciphering and combining functional and structural investigations ( Patarroyo et al., 2020 ).While Pv DBP may still be required for the invasion of Duffy negative erythrocytes ( Gunalan et al., 2018 ; Lo et al., 2019 ), the only focus on Pv DBP as a vaccine candidate certainly needs to be reconsidered, and alternative targets explored as potential substitutes for Pv DBP or in conjunction with it. A vaccine targeting only a single-stage parasite antigen faces challenges in retaining similar antibody responses due to the genomic changes in parasite ligands which in turn might improve the fitness of P. vivax isolates.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that a vaccine with multiple DBPII variant alleles is necessary for broader coverage. For finding new interaction hotspots to which malaria elimination approaches can be directed, a profound analysis is needed to correlate structural, functional (adhesion, invasion, and inhibition), and polymorphism data ( Patarroyo et al., 2020 ). Moreover, a blood stage vaccine has to face a huge number of merozoites in comparison to a few as in case of pre-erythrocytic and transmission blocking stage.…”
Section: Discussionmentioning
confidence: 99%
“…The Duffy blood group antigen, also known as the Duffy antigen/receptor for chemokines (DARC) or the FY gene, has been found as a scavenger on the surface of RBCs that removes excesses of circulating harmful chemokines. This is the key molecule that allows Plasmodium vivax and Plasmodium knowlesi parasites to invade red cells via the P. vivax Duffy binding protein (PvDBP) [45]. Because polymorphisms modify the binding to the parasite's DBP and the density of the antigen on the erythrocyte surface, different susceptibilities to P. vivax have been linked to the Duffy blood group antigens [46].…”
Section: Duffy Antigenmentioning
confidence: 99%